2008
DOI: 10.1037/0033-2909.134.5.662
|View full text |Cite
|
Sign up to set email alerts
|

Visual search for faces with emotional expressions.

Abstract: The goal of this review is to critically examine contradictory findings in the study of visual search for emotionally expressive faces. Several key issues are addressed: Can emotional faces be processed preattentively and guide attention? What properties of these faces influence search efficiency? Is search moderated by the emotional state of the observer? The authors argue that the evidence is consistent with claims that (a) preattentive search processes are sensitive to and influenced by facial expressions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
267
3
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(284 citation statements)
references
References 124 publications
(227 reference statements)
12
267
3
2
Order By: Relevance
“…A handful of studies have shown that animals (regardless of threat-relevance) are detected more quickly than plants [17][18][19] ; comparing snakes and spiders to other animals would rectify this potential issue [3][4] . Similar attention should be paid to choosing appropriate distracter stimuli for visual detection studies as threatening distracters have been shown to slow down participants when they are detecting non-threatening targets [20][21][22][23][24][25][26] . Using uniform distracters might help ensure that any differences found in detection can be attributed to the targets 7 .…”
Section: Discussionmentioning
confidence: 99%
“…A handful of studies have shown that animals (regardless of threat-relevance) are detected more quickly than plants [17][18][19] ; comparing snakes and spiders to other animals would rectify this potential issue [3][4] . Similar attention should be paid to choosing appropriate distracter stimuli for visual detection studies as threatening distracters have been shown to slow down participants when they are detecting non-threatening targets [20][21][22][23][24][25][26] . Using uniform distracters might help ensure that any differences found in detection can be attributed to the targets 7 .…”
Section: Discussionmentioning
confidence: 99%
“…We used schematic face stimuli to minimize complications from expression ambiguity and lack of standardization associated with variations in photographic stimuli (Frischen, Eastwood, & Smilek, 2008). Target stimuli were positive ('happy') and negative ('sad') faces, and left-and right-pointing arrows inside a circle were equiprobable and randomized within each block, resulting in 50% congruent trials (target location at response hand) and 50% incongruent trials (target location opposite to response hand).…”
Section: Experiments 1 Methodsmentioning
confidence: 99%
“…While improved search for faces with robust representations has been found (own face compared to unfamiliar faces, Tong & Nakayama, 1999), most studies using visual search paradigms for faces have focused on face "pop-out" in search such as detecting emotional faces (see Frischen, Eastwood, &,Smilek, (2008) for a review). Therefore, predictions about face search for unfamiliar faces and for multiple faces amongst distractor faces must come from experiments using stimuli other than faces.…”
Section: Dual-target Cost In Visual Search For Multiple Unfamiliar Facesmentioning
confidence: 99%